The Effect of Good Corporate Governance (GCG) on Financial Performance with Gender Diversity as a Moderating: Empirical Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 Period - Azka Afifa; Mariana Mariana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) mechanisms proxied by the board of commissioners, audit committee, and audit firm reputation on financial performance, with gender diversity as a moderating variable, in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The increasing complexity and risk in the property sector highlight the importance of effective governance in maintaining firm performance. Financial performance is measured using Return on Assets (ROA). This research employs a quantitative approach using secondary data obtained from 48 companies (240 observations) in the property and real estate sector over five years. The results indicate that the board of commissioners does not have a significant effect on financial performance, while the audit committee and audit firm reputation have a significant positive effect. Furthermore, gender diversity is not able to moderate the effect of the board of commissioners on financial performance. However, gender diversity significantly moderates the effect of the audit committee on financial performance by weakening it. These findings indicate that the effectiveness of GCG mechanisms varies and that the role of gender diversity depends on the governance structure.